ANALISIS SIFAT KEKUATAN TARIK DAN KEKUATAN BENDING KOMPOSIT HIBRYD SERAT LIDAH MERTUA DAN KARUNG GONI DENGAN FILLER ABU SEKAM PADI 5% BERMATRIK EPOXY - Muslim, Jauhari; Sari, Nasmi Herlina; Sulistyowati, Emmy Dyah (Dinamika Teknik Mesin, 2013)
Abstract The use of composite materials is growing at over the development of manufacturing industry. Composites sansevieria and hibiscus canabinus with the addition of rice husk ash filler. The purpose of this study was to analyze the tensile strength and bending strength of hybrid composites sansevieria and hybiscus canabinus with rice husk ash filler epoxy bermatrik with random fiber direction.Variation of fiber volume fraction sansevieria and hybicus canabinus is 0%:35%,10%:25%, 15%:10%, 20%:15%, 25%:10%, 35%:0%. Method for making composite specimens in the form of hand lay up with a fiber length of 2cm. Testing was done by bending test following the ASTM standard D790 tensile test and ASTM D3039 standards.The results showed that the composites with rice husk ash fillers higher bending strength and the strength of its appeal compared to the composite without using rice husk ash fillers, where the highest bending strength on volume fraction 0%/35% as big as 32,00 MPa (using filler), and kekutan lowest bending the volume fraction 0%/35% as big as 21, 69 Mpa (without filler). While the tensile test has the highest power in the volume fraction 15%/20% as big as 8,24 MPa (using filler), and the lowest tensile strength on volume fraction 0%/35%  as big as 3,43 MPa (without filler).